4x+12=10x-6

Simple and best practice solution for 4x+12=10x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+12=10x-6 equation:


Simplifying
4x + 12 = 10x + -6

Reorder the terms:
12 + 4x = 10x + -6

Reorder the terms:
12 + 4x = -6 + 10x

Solving
12 + 4x = -6 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
12 + 4x + -10x = -6 + 10x + -10x

Combine like terms: 4x + -10x = -6x
12 + -6x = -6 + 10x + -10x

Combine like terms: 10x + -10x = 0
12 + -6x = -6 + 0
12 + -6x = -6

Add '-12' to each side of the equation.
12 + -12 + -6x = -6 + -12

Combine like terms: 12 + -12 = 0
0 + -6x = -6 + -12
-6x = -6 + -12

Combine like terms: -6 + -12 = -18
-6x = -18

Divide each side by '-6'.
x = 3

Simplifying
x = 3

See similar equations:

| 12q+6=6q+6 | | A=4b^2-11 | | 3(p+4)=2(3p+1)-20 | | 2x=1+x^2+y^2 | | 2x+2y=1+x^2+y^2 | | A=4b-11 | | 5x+48=7x-10 | | 8+2overz=10 | | 0.9x-5.6=0.8x+2.7 | | 18000+x=90000 | | 10X+2=8x-5 | | 4x^2-9y^2-4x-6y=0 | | Y=p(x-5) | | (-9x+6)(-7x-10)=0 | | (-9a-7)(14a-11)-(-12a+15)(-9a-7)=0 | | 16625/475 | | x^2-y^2-4x+6y+3=0 | | x=10+0.001x | | (-2x-6)/11 | | y=4kx-3 | | 2x^2-4y^2+12x+24y+18=0 | | (10x+9)(-4x-11)=0 | | X-(-3)=18-16 | | 105000/(500000-350000)=0 | | (-5b-7)(4b+3)-(-10b+7)(-5b-7)=0 | | =2.72+0.772 | | (3b+11)(7b+4)-(5b-10)(3b+11)=0 | | 4=120/2x | | 4=120.2x | | (15a-15)(-7a+12)-(-9a-8)(15a-15)=0 | | 8m+6m-6n+7n= | | -4x^3-3X^2-4x=0 |

Equations solver categories